Immunometabolic factors in adolescent chronic disease are associated with Th1 skewing of invariant Natural Killer T cells - Ververs, FA; Engelen, SE; Nuboer, R; Vastert, B; van der Ent, CK; Van't Land, B; Garssen, J; Monaco, C; Boes, M; Schipper, HS (Springer Nature, 2021)
Invariant Natural Killer T (iNKT) cells respond to the ligation of lipid antigen-CD1d complexes via their T-cell receptor and are implicated in various immunometabolic diseases. We considered that immunometabolic factors might affect iNKT cell function. To this end, we investigated iNKT cell phenotype and function in a cohort of adolescents with chronic disease and immunometabolic abnormalities. We analyzed peripheral blood iNKT cells of adolescents with cystic fibrosis (CF, n = 24), corrected coarctation of the aorta (CoA, n = 25), juvenile idiopathic arthritis (JIA, n = 20), obesity (OB, n = 20), and corrected atrial septal defect (ASD, n = 25) as controls. To study transcriptional differences, we performed RNA sequencing on a subset of obese patients and controls. Finally, we performed standardized co-culture experiments using patient plasma, to investigate the effect of plasma factors on iNKT cell function. We found comparable iNKT cell numbers across patient groups, except for reduced iNKT cell numbers in JIA patients. Upon ex-vivo activation, we observed enhanced IFN-γ/IL-4 cytokine ratios in iNKT cells of obese adolescents versus controls. The Th1-skewed iNKT cell cytokine profile of obese adolescents was not explained by a distinct transcriptional profile of the iNKT cells. Co-culture experiments with patient plasma revealed that across all patient groups, obesity-associated plasma factors including LDL-cholesterol, leptin, and fatty-acid binding protein 4 (FABP4) coincided with higher IFN-γ production, whereas high HDL-cholesterol and insulin sensitivity (QUICKI) coincided with higher IL-4 production. LDL and HDL supplementation in co-culture studies confirmed the effects of lipoproteins on iNKT cell cytokine production. These results suggest that circulating immunometabolic factors such as lipoproteins may be involved in Th1 skewing of the iNKT cell cytokine response in immunometabolic disease.